2021
DOI: 10.3389/fimmu.2021.613729
|View full text |Cite
|
Sign up to set email alerts
|

Sending Out Alarms: A Perspective on Intercellular Communications in Insect Antiviral Immune Response

Abstract: Viral infection triggers insect immune response, including RNA interference, apoptosis and autophagy, and profoundly changes the gene expression profiles in infected cells. Although intracellular degradation is crucial for restricting viral infection, intercellular communication is required to mount a robust systemic immune response. This review focuses on recent advances in understanding the intercellular communications in insect antiviral immunity, including protein-based and virus-derived RNA based cell-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…The high prevalence of both viruses in Gmm is in agreement with a previous study [43]. The asymptomatic infection implies sublethal replication and the ability of these viruses to silence or evade the immune system, likely through mechanisms such as apoptosis or miRNAs [75][76][77]. Prevalence in the whole population (and possibly all tissues, as our investigations were on the RNA extracted from the whole fly body) concurs with a previous study where both viruses were found in all sample pools of investigated tissues [43].…”
Section: Discussionsupporting
confidence: 91%
“…The high prevalence of both viruses in Gmm is in agreement with a previous study [43]. The asymptomatic infection implies sublethal replication and the ability of these viruses to silence or evade the immune system, likely through mechanisms such as apoptosis or miRNAs [75][76][77]. Prevalence in the whole population (and possibly all tissues, as our investigations were on the RNA extracted from the whole fly body) concurs with a previous study where both viruses were found in all sample pools of investigated tissues [43].…”
Section: Discussionsupporting
confidence: 91%
“…Total RNA was extracted from different tissues using TRIzol reagent (Invitrogen, USA), and cDNA was synthesized using TransScript One-Step gDNA Removal and cDNA Synthesis SuperMix (TransGen Biotech, China) according to the manufacturer's protocol. Using the prepared cDNA as a template, the qTOWER 3 Real-Time PCR Thermal Cycler System (Analytik Jena, Germany) and SYBR Green Kit (TaKaRa Bio, Japan) were used for RT-PCR according to the manufacturer's instructions. The housekeeping Eukaryotic translation initiation factor 4A (eIF4A) gene of B. mori was used as an internal reference gene.…”
Section: Quantitative Real Time Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Insects are a major group of arthropods, and the most diverse, numerous, and widely distributed group of animals on Earth. During their evolutionary process, insects have evolved a complex and efficient innate immune system to resist pathogen invasion [1][2][3]. Their immune system comprises interconnected cellular and humoral responses, including phagocytosis, encapsulation, activation of proteolytic cascades, activation of prophenoloxidase (proPO), and synthesis of potent antimicrobial peptides (AMPs) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…• In silico: 6 siRNAs were designed using bioinformatics tools and effectively inhibited their respective targets in prediction tools Ayyagari (2022) 5′UTR, RdPd, Helicase Frontiers in Drug Discovery frontiersin.org differentiation, and in some animals (e.g., mosquitoes), it participates in the immune response against viral genetic material (Siomi & Siomi, 2009;Wang, 2021). In fact, RNAi has been studied as a therapeutic platform for treating various genetic diseases, cancers and antiviral therapy (Sidahmed et al, 2014;Kristen et al, 2019;Kara et al, 2022).…”
Section: Sars-cov2mentioning
confidence: 99%